Factors influencing the effectiveness of marketing communication strategy in UniKL MICET / Aziemah Abdull Sattar@Ismail - Abdull Sattar@Ismail, Aziemah (Faculty of Business and Management, 2015)
Marketing strategy to a company is very important as to make the customers aware about company’s product. In addition, without marketing in a company, the company cannot be growth as well as other successful company. The main purpose of this study was to determine the relationship between Independent variable (advertising, telemarketing, event marketing and web marketing) and dependent variable (Factors influencing the effectiveness of marketing communication in UniKL MICET). This study was conducted in Taboh Naning, Melaka and aim is to address the most significant factor towards influencing the effectiveness of marketing communication in UniKL MICET. This study is focus to the UniKL MICET’s students and 100 questionnaires were gathered in this research. The questionnaires were used to obtain and collected the data from the respondent. The researcher use non-probability sampling is because the entire respondents are too large and randomly drawn in UniKL MICET. There has a few of sampling, and the researcher has decided to use convenience sampling technique for this study. Convenience sampling is type of non-probability sampling design, which it attempts to obtain a simple of convenient elements. Often respondent are selected because they happen to be in right place at right time, which is area UnikL MICET itself. Overall, it can be concluded that event marketing is the most effective strategy that UniKL MICET can be used more.